Several simple remarks concerning the attractiveness and usefulness of “Kangaroo” problems - Rudalevičienė, Regina; Kašuba, Romualdas (Lietuvos matematikos rinkinys, 2011)
In the paper some aspects of natural attractiveness and practical usefulness of “Kangaroo” problems for individual students and for the teaching of math are discussed.